Psychometric properties of the household food insecurity assess scale among households with tuberculosis patients in South India - Krishnamoorthy, Yuvaraj; Rajaa, Sathish; Ezhumalai, Komala; Knudsen, Selby; Horsburgh Jr, Robert; Hochberg, Natasha; Salgame, Padmini; Ellner, Jerrold; Prakash Babu, Senbagavalli; Sarkar, Sonali (Progress in Nutrition, 2022)
Background/AimWe conducted this study to assess the psychometric properties (construct validity and internal consistency) of the Household Food Insecurity Access Scale (HFIAS) in measuring household food insecurity among households with tuberculosis (TB) patients in South IndiaMethodsCross-sectional analysis of data from large-scale cohort study under RePORT-India consortium, conducted between 2014 and 2019 amongst three districts of South India (Pondicherry district in Puducherry, Villupuram and Cuddalore in Tamil Nadu. Households with newly diagnosed smear positive TB patients aged ≥6 years were selected as study participants. Construct validity of HFIAS was assessed through exploratory and confirmatory factor analysis. Reliability assessment was done through Cronbach’s alpha.ResultsWe found that 33.4% of the households with TB patients had food insecurity. The principal component analysis in this study found two-factor model for HFIAS, representing insufficient food quality and quantity. Both these factors explained 88% of the total variance. Confirmatory factor analysis also revealed acceptable goodness-of-fit indices for the two-factor model. The scale had very good internal consistency (Cronbach’s α=0.92).ConclusionThe HFIAS tool has showed good validity and reliability to measure household food insecurity among TB households in South India.